India’s Indo-Pacific Embrace - Chaturvedy, Rajeev Ranjan (2018)
India’s perspective on peace and prosperity in the Indo-Pacific was outlined by Prime Minister Narendra Modi during his recent visits to New Delhi’s maritime neighbours – Indonesia, Malaysia and Singapore.